Student Communal Space Optimization Using Space Syntax Method, Case Study: UIN Maulana Malik Ibrahim Malang (Campus 1) - Lestari, Meygaretta Ave; Izza, Aulia Nuraqiqotul; Kurniawan, Indra; Lestari, Wiji Suci; Faqihuddin, Muhammad Imam (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
Communal spaces are essential for students to engage in various activities on campus. Previous research on student communal spaces has primarily focused on the internal aspects of these spaces, such as their capacity to accommodate student activities, students' perceptions of the communal space, the social interactions that occur within them, and behavioral analyses of students in these spaces. Consequently, this study seeks to examine student communal spaces from an external perspective, specifically by investigating the connectivity and visibility of the surrounding environment to identify the most optimal areas that hold significant potential for development into student communal spaces. UIN Maulana Malik Ibrahim Malang has yet to provide high-quality and optimized communal spaces for students within the campus environment. Using the Space Syntax method, this study reveals three areas with the potential to be developed into student communal spaces on campus based on the results of Axial Graph Analysis (AGA) and Visibility Graph Analysis (VGA): the area between the Science and Technology Building and the Megawati Building, the area in front of the microteaching lab, and the grand staircase area. The findings of this study are expected to serve as recommendations for the university in planning the development of student communal spaces within the campus environment.